IMPROVING STUDENTS’ ACTIVITIES AND ACHIEVEMENTS OF LEARNING ENGLISH USING THINK PAIR SHARE MODEL IN SMPN MAUR IN THE ACADEMIC YEAR OF 2019/2020 - Didin Sumiyardi (Jurnal Perspektif Pendidikan, 2019)
This study aims to determine students’ learning activeness and improve students' English learning achievement after using Think Pair Share model. The research method used in this study is Classroom Action Research (Action Reseach) using 2 cycles. Each cycle consists of four stages: design, activity and observation, reflection. The instruments used was the observation sheets of teaching and learning activeness and English test. The research results of students' English learning activeness could be seen from the indicators: a) asking questions, ideas or pre-cycle responses 22.86% in the first cycle 45.57% and in the second cycle 96.67%. b) answer the pre-cycle questions 17.14% in the first cycle 45.71% and in the second cycle 71.43%. c) do the tasks and dare to advance in front of the pre-cycle class 25.71% in the first cycle 51.43% and in the second cycle 74.28%. d) refute or approve other students’ pre-cycle 11.43% cycle I 40% and cycle II 65.71%. Then, the results of students’ learning achievement in English could be seen from the indicator of the average value of students has increased in each cycle in the cycle average of student scores of 56.53 then in the first cycle to 67.84 and in the second cycle of 81, 31. The results showed that there were improvement of students’ activities and English achievement of the ninth grade students of SMP Negeri Maur through the think pair share learning model. Therefore, the use of think pair share learning model could increase the activeness and achievement of students' English learning in SMPN Maur in the academic year of 2019/2020. Keywords: Active learning, learning achievement, think pair share.